Sole mate-Electronic Shoes to Assist Visually Challenged - Rashmi R.; Swathi S.; Murari Hanisha; S. Rahul; Rashmi S. (International Journal of Optical Innovations & Research, 2024)
Making daily living easier has always been a goal of technological development. Everyone in today's fast-paced world uses technology to their advantage, except for some regions. Society. One of them is visually impaired and must contend with many difficulties on a regular basis. One of their biggest issues is getting around, such as crossing roads, taking trains, or going to public places, all of which frequently require human help. Occasionally, if support is not provided, they are left defenseless, resulting in the visually impaired being dependent on other kinds of assistance such as guide dogs and canes. These are undoubtedly the most conventional methods. But these methods are often not efficient and need a lot of training, without which it might be dangerous to themselves and others. Instead of a cane, a smart shoe is created in this instance because it is more effective and practical. This system includes an ultrasonic range finder circuit for obstacle detection, a Bluetooth module with GPS technology to provide voice guidance to the desired location, and in emergency situations, it will send an SMS alert to registered mobile numbers via the Android application. This system offers a user-friendly and accessible navigational aid for people who are blind or visually impaired, which is a wonderful help for artificial vision by giving details about the environment and the static and moving objects nearby.
Keywords: Bluetooth; LCD; Smart shoe; Ultrasonic Sensor; android application; renesas microcontroller; water sensor